SYSTEMATIC LITERATURE REVIEW: EFEKTIVITAS MODUL ADAPTIF FLIPPED CLASSROOM BAGI KETERLIBATAN DAN PEMAHAMAN MATEMATIS SISWA SEKOLAH DASAR - Waliah, Diyah Rutin; Rufiana, Intan Sari; Indra Dewi, Radeni Sukma (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to synthesize empirical evidence on the effect of adaptive learning modules within the Flipped Classroom model on elementary students’ learning engagement and mathematical understanding. A Systematic Literature Review (SLR) was conducted using the PRISMA 2020 protocol and the PICO framework. Data were collected from Scopus, Web of Science, ERIC, and ScienceDirect using keywords related to flipped classroom, adaptive learning modules, student engagement, and mathematical understanding in elementary education. The screening process yielded 50 relevant articles for in-depth analysis. The selected studies involved elementary students and used various research designs, including experiments, quasi-experiments, mixed methods, and qualitative studies. Instruments reported across studies included mathematics achievement tests, engagement observation sheets, questionnaires, learning activity records, and adaptive system log data. Data were analyzed using thematic synthesis and cross-study comparison. The findings show that adaptive learning modules in the Flipped Classroom model consistently enhance behavioral, emotional, and cognitive engagement. Most studies also report significant improvement in mathematical understanding, especially in conceptual understanding, retention, and problem-solving skills. Key challenges include limited teacher training, infrastructure readiness, and inconsistent implementation of adaptivity. In conclusion, adaptive modules in the Flipped Classroom model have strong potential to improve elementary mathematics learning outcomes and student engagement.